(untitled) (Universitas Scientiarum, 2012)
Objective. The assessment of water quality includes the analysis of both physical-chemical and microbiological parameters. However, none of these evaluates the biological effect that can be generated in ecosystems or humans. In order to define the most suitable organisms to evaluate the toxicity in the affluent and effluent of three drinking-water treatment plants, five acute toxicity bioassays were used, incorporating three taxonomic groups of the food chain. Materials and methods. The bioassays used were Daphnia magna and Hydra attenuata as animal models, Lactuca sativa and Pseudokirchneriella subcapitata as plant models, and Photobacterium leioghnathi as bacterial model. To meet this objective, selection criteria of the organisms evaluated and cluster analysis were used to identify the most sensitive in the affluent and effluent of each plant. Results. All organisms are potentially useful in the assessment of water quality by meeting four essential requirements and 17 desirable requirements equivalent to 100% acceptability, except P. leioghnathi which does not meet two essential requirements that are the IC50 for the toxic reference and the confidence interval. The animal, plant and bacterial models showed different levels of sensitivity at the entrance and exit of the water treatment systems. Conclusions. H. attenuata, P. subcapitata and P. leioghnathi were the most effective organisms in detecting toxicity levels in the affluents and D. magna, P. subcapitata and P. leioghnathi in the effluents. Key words: bioassays, cluster analysis, drinking water, raw water, toxicity.